Economic evaluation of hypertension screening in Iran using a Markov model - Rajabali Daroudi; Ali Akbari Sari; Mahmoud Zamandi; Elham Yousefi (PLoS ONE, 2025)
Introduction and purpose Hypertension is one of the most common non-communicable diseases in the world and plays a significant role in the occurrence of cardiovascular complications, including coronary heart disease (CHD) and strokes. Therefore, the purpose of this study is to conduct an economic evaluation of high blood pressure screening strategies in Iran in 2020. Method We did an economic evaluation of 9 blood pressure screening strategies, including screening annually or every two or three years from the ages of 30, 40, or 50, using the Markov model. The Markov model was designed and implemented based on the natural history of cardiovascular disease in the 2020 TreeAge Pro software. The quality-adjusted life years and the average cost of high blood pressure screening and treatment per person were estimated from society’s perspective for the lifetime. Input data of the model were derived from published literature, expert opinion, and available data sources. Findings All screening interventions were more costly and more effective compared to no screening. Five strategies, including screening every three years from the age of 50, 40, and 30 years and screening every two years and annually from the age of 30, were undominated. Incremental cost-effectiveness ratios for these strategies ranged from $PPP 2,675.20 to 20,466.83. Probabilistic sensitivity analysis indicated that, at a cost-effectiveness threshold close to one times the GDP per capita, screening every two or three years from age 30 had the highest cost-effectiveness, with probabilities of 0.522 and 0.44, respectively. Conclusion Based on the findings of the economic evaluation, all screening strategies are more cost-effective compared to no screening, and among the screening strategies, considering about one times the GDP per capita as the cost-effectiveness threshold, a screening strategy every two years, starting at the age of 30, is the most cost-effective strategy.